PHOTOCATALYTIC ACTIVITY OF T-ZRO2 AND ZRO2-HFO2 FOR METHYL ORANGE DEGRADATION REACTION - Fiorena Sekarsari, Hanu
As a result of a 29,19% increase in textile and textile product (TPT) industry, Indonesia became the country with the highest TPT waste pollutants among the G20 members. These pollutants contain azo dyes, toxic properties, and slow degradation rates. One of the efforts to reduce pollutants in water is the use of ZrO2 as a photocatalyst. Zirconia is a good photocatalyst material because it has relatively low band gap energy, is inert, and shows good photocatalytic activity under UV irradiation. The performance of zirconia material is more optimal in the tetragonal phase (t-ZrO2) than other phase form of zirconia, which can be obtained through pyrolysis of MOF type UiO-66. In addition, the presence of other metals is expected to increase photocatalytic activity. Hf metal is known to increase the material’s defect level, resulting in charge separation and limiting electron-hole recombination. The photocatalytic activity was tested against the degradation reaction of methyl orange by t-ZrO2 and ZrO2-HfO2 with variations of reaction incubation for 3, 5, and 7 days. The four materials have been successfully synthesized and have energy gap values of 5,15 eV; 5,19 eV; 5,21 eV; and 5,22 eV. From the test on methyl orange solution taken at 0, 30, 60, 90, 120, 180, 240, and 300 minutes with UV irradiation, for t-ZrO2 and ZrO2-HfO2 incubation 3, 5, and 7 days respectively, the percentage the degradation of methyl orange was 93,94; 71,98; 76,26; and 85,34.